2000
DOI: 10.5144/0256-4947.2000.229
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Register for Antenatal Care at Local Primary Health Care Centers

Abstract: Background:The purpose of this study was to investigate the extent of antenatal care coverage as well as causes for and factors associated with the failure of pregnant mothers to register for antenatal care. Patients and Methods: During 1997, a list was compiled for births in three urban and three rural primary health care centers in the Northern region of Saudi Arabia, which contained details as to whether or not the mothers had been registered for antenatal care during their pregnancy. A number of nonregistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…There are several investigations conducted in Saudi Arabia to assess quality of healthcare in different settings . However, none were conducted in Jazan region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several investigations conducted in Saudi Arabia to assess quality of healthcare in different settings . However, none were conducted in Jazan region.…”
Section: Discussionmentioning
confidence: 99%
“…There are several investigations conducted in Saudi Arabia to assess quality of healthcare in different settings. [7][8][9][10] However, none were conducted in Jazan region. A systematic review assessing quality of healthcare in PHCs in Saudi | 303 GOSADI Arabia reported a substantial variation in quality of healthcare among PHCs in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal care was reported to be available in both urban (67%) and rural (96%) areas (El-Gilany & Aref, 2000). The distances between PHCCs and patients' homes were reported to be acceptable and to provide easy access to centres (86%).…”
Section: Accessmentioning
confidence: 99%
“…ANC services are being provided in some of the PHCs [ 5 ]. ANC services at the PHCs facilitate part of prenatal care and serves as a bridge between the primary, secondary, and tertiary levels of health care through the early identification of any risk associated with the pregnancy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%